Assessment of associated impacts the inappropriate disposal of coffee waste on the behavior escape of the earthworms - Thode Filho, Sérgio; Souza, Leonardo Corrêa de; Jorge, Emanuele Nunes de Lima Figueiredo; Silva, Morgana de Luna Mortoni da; Guedes, Aline Santos de oliveira; Silva, Morgana de Luna Mortoni da; Franco, Heider Alves (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2017)
Earthworms are one of the organisms used in ecotoxicity tests. The species (Eisenia fetida) is the most common. This preference is due to its ability to poorly convert chemically broken organic wastes into stabilized material. This work aimed to investigate the earthworm avoidance response, simulating the inappropriate disposal of this residue in soil, besides identifying the pH of these samples after the avoidance test. For this experiment we worked with two groups. The test group, used percentages of the coffee waste added to the mass of sandy and loamy soil. It can be seen that there are excessively high prevention and control measures in the disposal of petroleum residues and agricultural agrochemicals than in coffee waste. Therefore, these results highlight the importance of greater control and prevention of inappropriate coffee waste disposal. However, although the limiting dosage for earthworms was significantly higher than that of the other pollutants observed (10% sandy soil and 5% loamy soil), and because it was a solid residue of organic origin, the coffe waste also rendered soil unsuitable for habitat of the earthworms.